Relational agency and teacher development: a CHAT analysis of a collaborative professional inquiry project with biology teachers - McNicholl, J (2013)
Teacher quality largely determines student outcomes and many argue for high quality teacher training and professional development (PD). Much PD has been heavily critiqued and what constitutes effective provision for teachers remains contested. Disenfranchisement of teachers, through neglect of prior expertise and failure to acknowledge teachers' working contexts, some argue, are to blame. A PD project with five biology teachers and a teacher educator, grounded within a cultural, historical activity theoretical (CHAT) tradition, was initiated to address these shortcomings. Edwards' concept of relational agency was employed to investigate and interpret teacher collaboration. Teachers' perceptions about the project were gathered using free-response questionnaires and semi-structured interviews, with the data being analysed using a CHAT framework. The positive impact on teacher practice reported here was related to having opportunities to own and be responsible for one's own and others' development, exploiting the distributed expertise available and supporting collaborative work. © 2013 © 2013 Association for Teacher Education in Europe.